Defining the undefinable: an analysis of definitions of community archives. Issue 8 (7th November 2019) - Welland, Sarah; Cossham, Amanda
Abstract : Purpose: This paper aims to explore definitions and notions of what a community archive is, and the tensions between different understandings of community archives. Design/methodology/approach: The paper is a critical analysis of community archives definitions and understanding from researchers and practitioners across the wider heritage information sector. Findings: Community archives are a growing area of interest for researchers because of the archives' intrinsic link to the community and their provision of the evidence of it. While discussion often focuses on a paradigm of transformative purpose, existing definitions around community archives continue to be tenuous, reflecting different real or perceived types and practices and the perspective of the author and the sector they work within. Variations in definition can also occur because of differences in perspective around theory and practice, with many practitioner-based definitions intrinsically bound with the community they represent. This can result in community archives being defined as "alternative" based on mainstream practice or "political" based on theoretical purview, or "meeting the needs of community" by the community archivists themselves. Research limitations/implications: The paper is conceptual and does not attempt to provide one definition that covers the perceived extent of community archives. It is part of work in progress on the nature of community archives and the impact such discourse may have on archival theory and practice. Originality/value: This paper provides an overview of some of the key issues and themes impacting a definition of community archives, and in doing so works towards a broader understanding the nature of community archives. In most cases, the concept of "community" seems to provide a common definitive element and practitioner definitions focus on addressing the needs of self-defined community to a greater or lesser extent.